Approaches on the selection of web cameras and calibration targets for stereo vision - Eren, Haluk; Celik, Umit; Poyraz, Mustafa (Ieee, 2006)
In this paper, it is studied on the calibration by using specified web cameras. The performance of 3D computer vision depends on the accuracy of camera parameters. Therefore, camera calibration is very crucial in stereo vision. In this study, the options and selection of the target object that is used by the process of camera calibration are reviewed and evaluated some results obtained by web cameras. Webcams' costs are low relatively to the other digital consumer cameras but cannot be acquired a high resolution image.
Stereo görü için Web kameralari ve kalibrasyon hedef seçimi üzerine yaklaşimlar
IEEE 14th Signal Processing and Communications Applications -- APR 16-19, 2006 -- Antalya, TURKEY